Camping with the Stars: Queer Perfomativity, Pop Intertextuality, and Camp in the Pop Art of Lady Gaga - Horn, Katrin (Current Objectives of Postgraduate American Studies, 2012)
The article is concerned with the possibility of employing countercultural and subversive strategies in U.S. mainstream media. The concept in question is camp, historically rooted in gay subculture, as performed by pop artist Lady Gaga. She is presented as challenging gender as well as aesthetic norms in her performances via the employment of camp—thus opening her public persona to queer readings.